Iron-copper diatomic catalyst with sustainable dual oxidation-reduction cycle as well as preparation method and application of iron-copper diatomic catalyst

By designing an iron-copper diatomic catalyst with sustainable dual redox cycles, the problem of poor performance of single atomic catalysts in redox cycles is solved, and efficient and sustainable catalytic degradation effect is achieved.

CN119793510APending Publication Date: 2025-04-11NANCHANG HANGKONG UNIVERSITY +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411986509.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing single-atom catalysts have problems such as slow active sites and metal ions leaching in the redox cycle, resulting in poor circulation performance and the redox cycle of the second metal is usually ignored.

Method used

An iron-copper diatom catalyst with a sustainable dual redox cycle is designed to perform complexation reactions by mixing organic acid ligands with soluble iron and copper salts, and a catalyst with an N4-Fe-Cu-N3 coordination structure is formed through self-assembly reactions and pyrolysis processes.

Benefits of technology

An efficient and sustainable dual redox cycle is achieved, which can efficiently activate hydrogen peroxide to degrade organic pollutants without adding cocatalysts or external energy, and has excellent catalytic degradation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793510A_ABST
    Figure CN119793510A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-copper diatomic catalyst with sustainable dual oxidation-reduction cycles as well as a preparation method and application of the iron-copper diatomic catalyst. A carrier of the iron-copper diatom catalyst is graphite phase carbon nitride, iron-copper diatoms are combined on the carrier through an N4-Fe-Cu-N3 coordination structure, and the coordination effect of the iron-copper diatoms enables the iron-copper diatom catalyst to efficiently activate hydrogen peroxide through continuous iron-copper dual redox cycle; the mass fractions of iron and copper diatoms in the catalyst are respectively 1%-10% and 3%-15%, so that the diatom catalyst capable of realizing the sustainable dual redox cycle can effectively activate hydrogen peroxide in the process of degrading organic pollutants, and meanwhile, the pollutants are efficiently degraded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of diatomic catalysts for degradation of refractory organic pollutants, and in particular to an iron-copper diatomic catalyst with sustainable dual redox cycles, and a preparation method and application thereof. Background Art

[0002] Single-atom catalysts have attracted extensive attention in the field of advanced oxidation processes due to their advantages such as maximizing the utilization of metal atoms, high efficiency and high selectivity. However, single-atom catalysts (SACs) have problems such as slow redox cycles at single active sites and metal ion leaching, resulting in poor cycle performance. In order to accelerate the redox cycle of single-atom active sites in SACs, diatomic catalysts with multiple active sites have emerged. The diatomic catalysts have advantages such as electronic effect, synergistic effect and steric effect, which improve the activity and stability of the catalyst. In diatomic catalysts with two sites, one active site usually provides electrons to promote the redox cycle of the target active site, especially multivalent metals such as Mo and Mn. However, the redox cycle of the second metal is usually ignored, or the redox cycle is promoted by introducing external energy or co-catalysts. Therefore, it is of great significance to design a dual-site catalyst with dual redox cycles to achieve efficient and sustainable Fenton-like reactions. Summary of the invention

[0003] The purpose of the present invention is to solve the technical problems existing in the prior art and to provide a method for preparing an iron-copper diatomic catalyst and its application.

[0004] To achieve the above object, the technical solution provided by the present invention is: a method for preparing an iron-copper diatomic catalyst with a sustainable dual redox cycle, the preparation method comprising the following steps:

[0005] Step 1: mixing an organic acid ligand and a soluble iron salt, and performing a complexation reaction under continuous magnetic stirring to obtain an iron-organic complex solution;

[0006] Step 2: mixing the organic acid ligand and the soluble copper salt, and carrying out a complex reaction under continuous magnetic stirring to obtain a copper-organic complex solution;

[0007] Step 3: uniformly mixing the iron-organic complex solution obtained in step 1 and the copper-organic complex solution obtained in step 2 with the cyanuric acid solution, and then pouring the mixed solution into the melamine solution to perform a self-assembly reaction to obtain a precursor;

[0008] Step 4: The precursor obtained in step 3 is pyrolyzed to obtain an iron-copper diatomic catalyst with a sustainable iron-copper dual redox cycle.

[0009] Preferably, the organic acid in step 1 and step 2 includes oxalic acid and citric acid; the soluble iron salt is ferric nitrate; the soluble copper salt is cupric acetate; and the molar ratio of ferric nitrate: cupric acetate is (1-10):(1-10).

[0010] Preferably, in step 3, the sum of the amount of the carboxyl substance in the organic acid ligand and the amount of the hydroxyl substance in cyanuric acid in the mixed solution is equal to the amount of the amino substance in the cyanamide compound.

[0011] Preferably, the temperature of the precursor pyrolysis in step 4 is 500-600° C., the pyrolysis time is 2-6 hours, and the pyrolysis process is carried out under a protective atmosphere.

[0012] The present invention also provides an iron-copper diatomic catalyst with a sustainable dual redox cycle prepared by the above-mentioned preparation method, wherein the carrier of the iron-copper diatomic catalyst is graphite phase carbon nitride, and the iron-copper diatoms are bound to the carrier in a N4-Fe-Cu-N3 coordination structure; the coordination effect of the iron-copper diatoms enables the iron-copper diatomic catalyst to efficiently activate hydrogen peroxide through a sustainable iron-copper dual redox cycle; the mass fractions of the iron-copper diatoms in the iron-copper diatomic catalyst are 1%-10% and 3%-15%, respectively.

[0013] Preferably, the loading amount of the iron-copper diatomic catalyst is 1%-2% and 5%-6% by mass, respectively.

[0014] The present invention also provides the use of the above-mentioned iron-copper diatomic catalyst with sustainable dual redox cycle in activating hydrogen peroxide to degrade organic pollutants. The iron-copper diatomic catalyst with sustainable dual redox cycle, hydrogen peroxide and organic pollutants to be treated are mixed, and the organic pollutants are degraded without adding additional energy, co-catalysts and sacrificial agents.

[0015] Beneficial effects of the present invention:

[0016] 1. The method for preparing the iron-copper diatomic catalyst provided by the present invention uses graphite phase carbon nitride as a carrier, wherein the graphite phase carbon nitride has abundant and uniformly located nitrogen atoms, which makes the surrounding environment of the iron-copper diatoms uniform, thereby enabling the diatomic catalyst provided by the present invention to have a sustainable dual redox cycle when activating hydrogen peroxide to degrade organic pollutants.

[0017] 2. The present invention also provides a method for preparing an iron-copper diatomic catalyst, which comprises mixing soluble iron salts, copper salts and water of different organic acids respectively, and conducting a complex reaction to obtain an iron-organic complex solution and a copper-organic complex solution respectively; mixing the iron-organic complex solution, the copper-organic complex solution, cyanuric acid and melamine to obtain a precursor; pyrolyzing the precursor to obtain the iron-copper diatomic catalyst with continuous dual redox cycle activation of hydrogen peroxide; the iron-copper diatomic catalyst can be successfully prepared, and the preparation method is simple to operate, has a wide source of raw materials, low production cost, and controllable iron-copper atom content.

[0018] 3. The diatomic catalyst provided by the present invention has high efficiency and strong anti-interference ability when used to activate hydrogen peroxide to degrade difficult organic pollutants, and has a dual redox cycle without adding a co-catalyst or external energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0020] Figure 1 The X-ray diffraction (XRD) patterns of FeCu-CN obtained in Example 1, Fe-CN obtained in Comparative Example 1, Cu-CN obtained in Comparative Example 2, and CN obtained in Comparative Example 3;

[0021] Figure 2 The Fourier transform infrared spectra (FT-IR) of FeCu-CN obtained in Example 1, Fe-CN obtained in Comparative Example 1, Cu-CN obtained in Comparative Example 2, and CN obtained in Comparative Example 3 are shown;

[0022] Figure 3 This is a transmission electron microscope (TEM) image of FeCu-CN obtained in Example 1;

[0023] Figure 4 Element distribution diagram of FeCu-CN obtained in Example 1;

[0024] Figure 5 This is a spherical aberration corrected high-angle annular dark field scanning transmission electron microscopy (AC-HAADF-STEM) image of FeCu-CN obtained in Example 1;

[0025] Figure 6 This is the X-ray absorption near edge structure (XANES) image of FeCu-CN obtained in Example 1;

[0026] Figure 7 The extended X-ray absorption fine structure (EXAFS) image of FeCu-CN obtained in Example 1;

[0027] Figure 8 This is the rate diagram of the degradation of sulfamethoxazole (SMX) by activating H2O2 with FeCu-CN obtained in Example 1;

[0028] Fig. 9 Nitroblue tetrazolium (NBT) and benzoic acid (BA) were used as O2 - and ·OH probe, the activation solution obtained by activating FeCu-CN obtained in Example 1, Fe-CN obtained in Comparative Example 1, and Cu-CN obtained in Comparative Example 2 with H2O2·O2 - Qualitative and quantitative test chart of OH;

[0029] Fig.10 5,5-Dimethyl-1-pyrroline-N-oxide (DMPO) was used as ·OH and ·O2 - As a probe, 2,2,6,6-tetramethylpiperidine (TEMP) was used 1 O2 probe, EPR graph of the activation solution obtained by activating H2O2 with FeCu-CN obtained in Example 1, Fe-CN obtained in Comparative Example 1, and Cu-CN obtained in Comparative Example 2;

[0030] Fig.11 This is a graph showing the active site capture experiment in the activation solution obtained by activating FeCu-CN obtained in Example 1, Fe-CN obtained in Comparative Example 1, and Cu-CN obtained in Comparative Example 2 with H2O2 using Ferrozine as Fe(II) complexing agent and Neocuproine (NCP) as C(I) complexing agent;

[0031] Fig.12 The X-ray photoelectron energy (XPS) spectra of Cu 2p in FeCu-CN obtained in Example 1 and Cu-CN obtained in Comparative Example 2 are shown;

[0032] Fig.13 This is a qualitative and quantitative test chart of O2 in the activation solution obtained by activating H2O2 with FeCu-CN obtained in Example 1. DETAILED DESCRIPTION

[0033] This section will describe in detail the specific embodiments of the present invention. The purpose of the drawings is to supplement the description of the text part of the specification with graphics, so that people can intuitively and vividly understand each technical feature and the overall technical solution of the present invention, but it should not be understood as a limitation on the scope of protection of the present invention.

[0034] Reference Figure 1-13 , a preferred embodiment of the present invention, a method for preparing an iron-copper diatomic catalyst with a sustainable dual redox cycle, the preparation method comprising the following steps:

[0035] Step 1: Mixing an organic acid ligand and a soluble iron salt, and carrying out a complexation reaction under continuous magnetic stirring (the temperature of the complexation reaction is preferably room temperature; the time is preferably 5 to 20 minutes) to obtain an iron-organic complex solution;

[0036] Step 2: Mixing the organic acid ligand and the soluble copper salt, and carrying out a complex reaction under continuous magnetic stirring (the temperature of the complex reaction is preferably room temperature; the time is preferably 5 to 20 minutes) to obtain a copper-organic complex solution;

[0037] Step 3: After uniformly mixing the iron-organic complex solution obtained in step 1 and the copper-organic complex solution obtained in step 2 with the cyanuric acid solution, the mixed solution is poured into the melamine solution to carry out a self-assembly reaction (preferably for 2-10 hours, more preferably for 3-5 hours). The obtained precipitate is washed and dried to obtain a precursor;

[0038] Step 4: The precursor obtained in step 3 is pyrolyzed to obtain an iron-copper diatomic catalyst with a sustainable iron-copper dual redox cycle.

[0039] Furthermore, in step 1, the mass ratio of the organic acid to the iron salt is preferably 0.432:(0.096-0.969), and more preferably 0.432:0.096; in step 2, the mass ratio of the organic acid to the copper salt is preferably 1.008:(0.0479-0.479), and more preferably 1.008:0.239; the mass ratio of the iron salt to the copper salt is preferably (0.096-0.969):(0.0479-0.479), and more preferably 0.096:0.239.

[0040] Furthermore, in step 3, the sum of the amount of the carboxyl group in the organic acid ligand and the amount of the hydroxyl group in cyanuric acid in the mixed solution is equal to the amount of the amino group in the cyanamide compound.

[0041] The mass ratio of the soluble iron salt, the soluble copper salt, cyanuric acid and melamine is preferably (0.096-0.969):(0.0479-0.479):(1-4):(1-4), and more preferably 0.096:0.239:1.834:3.027.

[0042] The iron-organic complex solution, the copper-organic complex, cyanuric acid and melamine self-assemble to form supramolecules through intermolecular hydrogen bonds, thereby fixing the metal ions. In the subsequent pyrolysis process, the iron-copper atoms are evenly loaded on the carrier.

[0043] Furthermore, in step 4, the temperature of the precursor pyrolysis is 500-600°C, the pyrolysis time is 2-6h, and the pyrolysis process is carried out under a protective atmosphere (the protective atmosphere preferably includes argon or nitrogen); the pyrolysis can cause the supramolecular precursor to form carbon-doped graphite phase carbon nitride; at the same time, the copper ions are converted into a single atomic state.

[0044] The preparation method disclosed in the present invention can successfully prepare an iron-copper diatomic catalyst, and the preparation method is simple to operate, has a wide source of raw materials, low production cost, and controllable iron-copper atomic content.

[0045] The present invention also discloses an iron-copper diatomic catalyst with sustainable dual redox cycle prepared by the above-mentioned preparation method, wherein the carrier of the iron-copper diatomic catalyst is graphite phase carbon nitride, and the iron-copper diatoms are bound to the carrier in a N4-Fe-Cu-N3 coordination structure; the coordination effect of the iron-copper diatoms enables the iron-copper diatomic catalyst to efficiently activate hydrogen peroxide through a sustainable iron-copper dual redox cycle; the mass fractions of the iron-copper diatoms in the iron-copper diatomic catalyst are 1%-10% and 3%-15% respectively.

[0046] Furthermore, the loading amounts of the iron-copper diatomic catalysts account for 1%-2% and 5%-6% of the mass fraction of the iron-copper diatomic catalysts, respectively.

[0047] Specifically, the iron-copper diatomic catalyst uses graphite phase carbon nitride as a carrier, wherein the graphite phase carbon nitride has abundant and uniformly located nitrogen atoms, which makes the surrounding environment of the iron-copper diatoms uniform, thereby enabling the diatomic catalyst provided by the present invention to have a sustainable dual redox cycle when activating hydrogen peroxide to degrade organic pollutants.

[0048] The present invention also discloses the use of the above-mentioned iron-copper diatomic catalyst with sustainable dual redox cycle in activating hydrogen peroxide to degrade organic pollutants. The iron-copper diatomic catalyst with sustainable dual redox cycle, hydrogen peroxide and organic pollutants to be treated are mixed, and the organic pollutants are degraded without adding additional energy, co-catalysts and sacrificial agents.

[0049] Further, the mass ratio of the iron-copper diatomic catalyst to hydrogen peroxide is preferably (5-30):(3-25), and further preferably (10-20):(15-25);

[0050] Furthermore, the mass ratio of the iron-copper diatomic catalyst to the organic pollutant to be treated is preferably (10-20):(1-5); and the degradation temperature is preferably room temperature.

[0051] Example 1

[0052] (1) Weigh 0.423 g of oxalic acid and 0.096 g of ferric nitrate, add them to 90 mL of deionized water and dissolve them to obtain solution A;

[0053] (2) Weigh 1.008 g of citric acid and 0.239 g of copper acetate, add them to 90 mL of deionized water and dissolve them to obtain solution B;

[0054] (3) Weigh 1.834 g of cyanuric acid and 3.027 g of melamine, add 300 mL of deionized water, and heat at 85° C. to dissolve to obtain solutions C and D;

[0055] (4) mixing solutions A and B with C simultaneously to obtain solution E;

[0056] (5) Solution D was added to solution E and mixed, and after stirring for 4 h, the mixture was filtered, washed, and dried at 60 °C for 24 h to obtain a precursor;

[0057] (6) The precursor was placed in a tube furnace, and the temperature was raised to 600°C at a rate of 5°C / min under an argon atmosphere and kept at this temperature for 4 h. The obtained iron-copper diatomic catalyst was recorded as FeCu-CN. The ICP-MS test showed that the iron and copper contents in the diatomic catalyst were 1.0% and 5.0%, respectively.

[0058] Comparative Example 1

[0059] (1) Weigh 0.423 g of oxalic acid and 0.096 g of ferric nitrate, add them to 90 mL of deionized water and dissolve them to obtain solution A;

[0060] (2) Weigh 2.456 g of cyanuric acid and 3.027 g of melamine, add 300 mL of deionized water, and heat at 85° C. to dissolve to obtain solutions B and C;

[0061] (4) mixing solutions A and B to obtain solution D;

[0062] (5) Solution C was added to D and mixed, and the mixture was filtered, washed, and dried at 60° C. for 24 h to obtain a precursor;

[0063] (6) The precursor was placed in a tube furnace, heated to 600° C. at 5° C. / min under an argon atmosphere and kept at this temperature for 4 h. The obtained iron single atom catalyst was denoted as Fe-CN. The ICP-MS test showed that the iron content in the single atom was 1.0%.

[0064] Comparative Example 2

[0065] (1) Weigh 1.008 g of citric acid and 0.239 g of copper acetate, add them to 90 mL of deionized water and dissolve them to obtain solution A;

[0066] (2) Weigh 2.456 g of cyanuric acid and 3.027 g of melamine, add 300 mL of deionized water, and heat at 85° C. to dissolve to obtain solutions B and C;

[0067] (4) mixing solutions A and B to obtain solution D;

[0068] (5) Solution C was added to D and mixed, and the mixture was filtered, washed, and dried at 60° C. for 24 h to obtain a precursor;

[0069] (6) The precursor was placed in a tube furnace, and the temperature was raised to 600° C. at 5° C. / min under an argon atmosphere and kept at this temperature for 4 h. The obtained copper single atom catalyst was recorded as Cu-CN. The ICP-MS test showed that the copper content in the single atom was 5.0%.

[0070] Comparative Example 3

[0071] (1) Weigh 3.004 g of cyanuric acid and 3.027 g of melamine, add 300 mL of deionized water, and heat to 80° C. to dissolve to obtain solutions A and B;

[0072] (2) Solutions A and B were mixed, stirred for 4 h, filtered, washed, and dried at 60 °C for 24 h to obtain a precursor;

[0073] (3) The precursor was placed in a tube furnace, heated to 600°C at a rate of 5°C / min under an argon atmosphere and kept at this temperature for 4 h. The obtained graphite phase carbon nitride catalyst was recorded as CN.

[0074] Figure 1 and Figure 2 The XRD patterns and FT-IR patterns of FeCu-CN obtained in Example 1, Fe-CN obtained in Comparative Example 1, Cu-CN obtained in Comparative Example 2, and CN obtained in Comparative Example 3 are shown respectively. Figure 1 It can be seen that the iron-copper diatomic catalyst prepared in Example 1 has diffraction peaks at 13.1° and 27.8°, which correspond to the (100) and (002) crystal plane diffraction characteristic peaks of graphite phase carbon nitride, respectively, and no diffraction peaks of iron or copper and their compounds appear; Figure 2 See, 807cm -1 The peaks at 1700-1200 cm -1 Characteristic absorption peaks corresponding to the stretching vibration modes of heterocyclic and aromatic CN appeared. The above results show that the carrier of FeCu-CN is CN.

[0075] Figure 3 and Figure 4 They are respectively the TEM image and element distribution map of FeCu-CN obtained in Example 1. It can be seen from the figure that no clusters and nanoparticles are observed, and each element is evenly dispersed.

[0076] Figure 5 This is the AC-HAADF-STEM image of FeCu-CN obtained in Example 1. It can be seen that Fe and Cu are evenly distributed on CN.

[0077] Figure 6 This is the XANES of FeCu-CN obtained in Example 1, where a is Fe K-Edge and b is Cu K-Edge. Figure 6 As shown in the figure: the Fe near edge in FeCu-CN is located between the Fe foil and the FeO benchmark, indicating that the valence state of Fe is between 0 and +2, closer to +2; the Cu near edge in FeCu-CN is located between the Cu2O and CuO benchmarks, indicating that the valence state of Cu is between +1 and +2, closer to +1. In order to accurately obtain the coordination environment of Fe and Cu diatoms, the EXAFS of FeCu-CN is fitted and analyzed ( Figure 7 ), the average coordination numbers of Fe-N, Cu-N and Fe-Cu were 4, 3 and 1, respectively, confirming that the diatomic FeCu-CN is a N4-Fe-Cu-N3 coordination structure.

[0078] Figure 8 The degradation effect diagram of SMX activated by H2O2 is shown in the figure for FeCu-CN obtained in Example 1, Fe-CN obtained in Comparative Example 1, Cu-CN obtained in Comparative Example 2, and CN obtained in Comparative Example 3 (reaction conditions: 50mL, 0.4g / L catalyst, 10mM H2O2). As shown in the figure, the degradation order of SMX is FeCu-CN>Cu-CN>Fe-CN>CN. In addition, the degradation rate of SMX by FeCu-CN is 20 and 4 times that of Fe-CN and Cu-CN, respectively. The degradation of SMX by the mixture of Fe-CN and Cu-CN alone has no enhancing effect, indicating that the Fe and Cu in the diatomic FeCu-CN catalyst have a synergistic enhancing effect on the activation of H2O2.

[0079] Fig. 9 In order to use nitroblue tetrazolium (NBT) and benzoic acid (BA) as O2 - The Fe-CN obtained in Comparative Example 1, the Cu-CN obtained in Comparative Example 2, and the FeCu-CN obtained in Example 1 activated with H2O2 were tested by ·O2 in the activated solution. - and ·OH, where: ac is ·O2 in the activated solution - d is the UV absorption spectrum of the obtained activation solution, and d is the quantitative test diagram of ·OH in the obtained activation solution. Fig. 9 As shown in the figure, with the progress of reaction time, the activation solution obtained by FeCu-CN activating H2O2 has a large amount of O2 -and ·OH increased, and the activation solution obtained by FeCu-CN activating H2O2 contained ·O2 - The source of is mainly Cu in active sites.

[0080] 5,5-Dimethyl-1-pyrroline-N-oxide (DMPO) was used as ·OH and ·O2 - As a probe, 2,2,6,6-tetramethylpiperidine (TEMP) was used 1 The FeCu-CN obtained in Example 1, the Fe-CN obtained in Comparative Example 1, and the Cu-CN obtained in Comparative Example 2 activated with H2O2 were subjected to EPR testing. The results are as follows: Fig.10 As shown. Fig.10 It can be seen that the activation solution obtained by FeCu-CN activation of H2O2 detected ·OH and ·O2 - The characteristic peaks of ·OH and ·O2 - However, no O2 was detected in the activation solution obtained by Fe-CN activation of H2O2 - This also shows that the activation solution obtained by FeCu-CN activating H2O2 contains ·O2 - The source of is mainly active site Cu. 2,2,6,6-tetramethylpiperidine (TEMP) is used as 1 When the probe of O2 was used, the activation solution obtained by activating H2O2 with FeCu-CN obtained in Example 1, Fe-CN obtained in Comparative Example 1, and Cu-CN obtained in Comparative Example 2 was detected. 1 O2 characteristic peaks indicate that there is no 1 The above results show that FeCu-CN activates H2O2 to produce ·OH and ·O2 - .

[0081] Ferrozine was used as Fe(II) complexing agent and Neocuproine (NCP) was used as Cu(I) complexing agent to capture active sites in the activation solution obtained by activating FeCu-CN obtained in Example 1, Fe-CN obtained in Comparative Example 1, and Cu-CN obtained in Comparative Example 2 with H2O2. The results are as follows: Fig.12 As shown in the figure, the degradation of SMX was inhibited by adding Ferrozine and NCP, respectively, indicating that Fe(II) and Cu(I) were dual active sites in the reaction system.

[0082] Fig.12 is the Cu 2p X-ray photoelectron spectrum (XPS), wherein: a is the Cu 2p XPS spectra of FeCu-CN obtained in Example 1 and Cu-CN obtained in Comparative Example 2, b is the Cu 2p XPS spectra of FeCu-CN obtained in Example 1

[0083] XPS spectra of Cu 2p before and after the FeCu-CN reaction. Fig.12 As shown, the Cu 2p spectrum is fitted with two double peaks at 932.4 / 952.2 eV and 935.5 / 955.4 eV, corresponding to Cu(Ⅰ) and Cu(II), respectively.

[0084] As shown in Figure a, the content of Cu(II) in FeCu-CN is higher than that in Cu-CN, which indicates that the Cu in FeCu-CN may provide electrons for Fe. As shown in Figure b, the content of Cu(I) in FeCu-CN slightly decreased from 73.5% to 72.6% before and after the reaction, which indicates that electrons were transferred from Cu(I) to Fe, thereby promoting the reduction of Fe(III) to Fe(II). In addition, O2( Fig.13 ), indicating that O2 - As a reducing agent, it promotes the reduction of Cu(II). The above results show that Cu(I) and ·O2 - The presence of promotes the Fe-Cu dual redox cycle in FeCu-CN activated H2O2.

[0085] The FeCu-CN prepared by the present invention activates H2O2 to degrade organic pollutants. Through material characterization, qualitative and quantitative analysis of active substances and analysis of active species, it is found that FeCu-CN activates H2O2 to achieve

[0086] The Fe-Cu dual redox cycle makes it highly efficient and has strong anti-interference ability in degrading organic pollutants.

[0087] The advantages of the FeCu-CN of the present invention are: 1. Fe and Cu atoms are evenly distributed, and the active site Cu in FeCu-CN can provide electrons for the active site Fe; 2. FeCu-CN activates Cu(I) and·O2 in H2O2 - The presence of promotes the Fe-Cu dual redox cycle; 3. The catalytic degradation efficiency is high, the anti-interference ability is strong and has good practical application ability, especially the FeCu-CN catalyst prepared in Example 1, which has extremely excellent catalytic degradation performance without adding a promoter or external energy. This work provides a demonstration for sustainable dual redox in the efficient treatment of organic pollutant wastewater.

[0088] Under the premise that no conflict occurs, those skilled in the art may freely combine and superimpose the above-mentioned additional technical features.

[0089] The above description is only a preferred implementation mode of the present invention. Any technical solution that achieves the purpose of the present invention by substantially the same means belongs to the protection scope of the present invention.

Claims

1. A method for preparing an iron-copper diatomic catalyst with a sustainable dual redox cycle, characterized in that: The preparation method comprises the following steps: Step 1: mixing an organic acid ligand and a soluble iron salt, and carrying out a complexation reaction under continuous magnetic stirring to obtain an iron-organic complex solution; Step 2: mixing the organic acid ligand and the soluble copper salt, and carrying out a complex reaction under continuous magnetic stirring to obtain a copper-organic complex solution; Step 3: uniformly mixing the iron-organic complex solution obtained in step 1 and the copper-organic complex solution obtained in step 2 with the cyanuric acid solution, and then pouring the mixed solution into the melamine solution to perform a self-assembly reaction to obtain a precursor; Step 4: The precursor obtained in step 3 is pyrolyzed to obtain an iron-copper diatomic catalyst having a sustainable iron-copper dual redox cycle.

2. The method for preparing an iron-copper diatomic catalyst with a sustainable dual redox cycle according to claim 1, characterized in that: The organic acid in step 1 and step 2 includes oxalic acid and citric acid; the soluble iron salt is ferric nitrate; the soluble copper salt is copper acetate; the molar ratio of ferric nitrate:copper acetate is (1-10):(1-10).

3. The method for preparing an iron-copper diatomic catalyst with a sustainable dual redox cycle according to claim 1, characterized in that: In step 3, the sum of the amount of the carboxyl group in the organic acid ligand and the amount of the hydroxyl group in cyanuric acid in the mixed solution is equal to the amount of the amino group in the cyanamide compound.

4. The method for preparing an iron-copper diatomic catalyst with a sustainable dual redox cycle according to claim 1, characterized in that: In step 4, the temperature of the precursor pyrolysis is 500-600° C., the pyrolysis time is 2-6 hours, and the pyrolysis process is carried out under a protective atmosphere.

5. The iron-copper diatomic catalyst with sustainable dual redox cycle prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The carrier of the iron-copper diatomic catalyst is graphite phase carbon nitride, and the iron-copper diatoms are bound to the carrier in a N4-Fe-Cu-N3 coordination structure; the coordination effect of the iron-copper diatoms enables the iron-copper diatomic catalyst to efficiently activate hydrogen peroxide through a continuous iron-copper dual redox cycle; the mass fractions of the iron-copper diatoms in the iron-copper diatomic catalyst are 1%-10% and 3%-15%, respectively.

6. The iron-copper diatomic catalyst with sustainable dual redox cycle according to claim 5, characterized in that: The loading amounts of the iron-copper diatomic catalysts are 1%-2% and 5%-6% by mass.

7. Use of an iron-copper diatomic catalyst with a sustainable dual redox cycle in activating hydrogen peroxide to degrade organic pollutants according to claim 5 or 6, characterized in that: An iron-copper diatomic catalyst with a sustainable dual redox cycle, hydrogen peroxide and the organic pollutants to be treated are mixed to degrade the organic pollutants without adding additional energy, co-catalysts or sacrificial agents.

Citation Information

Cited By

  • Quaternary ammonium modified iron-doped graphite phase carbon nitride Fenton catalyst as well as preparation method and application thereof

    CN121648949A